2014
DOI: 10.1177/1352458514549402
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular adaptations to long-term progressive resistance training translates to improved functional capacity for people with multiple sclerosis and is maintained at follow-up

Abstract: Compelling evidence is provided, that PRT performed over sufficiently long periods, improves functional capacity, likely due to neuromuscular adaptations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 35 publications
3
71
0
8
Order By: Relevance
“…This deficit is due to deficient muscle mechanical parameters related to both neural [6,11] and structural [12] mechanisms. Indeed, previous studies have shown loss of muscle mass, abnormal distribution of muscle fiber types, reduced ability to fully activate motor units, and reduced rate of force development in patients with MS when compared with nondisabled controls [5,13].…”
Section: Introductionmentioning
confidence: 96%
“…This deficit is due to deficient muscle mechanical parameters related to both neural [6,11] and structural [12] mechanisms. Indeed, previous studies have shown loss of muscle mass, abnormal distribution of muscle fiber types, reduced ability to fully activate motor units, and reduced rate of force development in patients with MS when compared with nondisabled controls [5,13].…”
Section: Introductionmentioning
confidence: 96%
“…Given the influence of ambulation on everyday life activities, gait impairment has been a target of rehabilitation strategies and of dalfampridine, a broad spectrum potassium channel blocker that is the only US Food and Drug Administration-approved symptomatic treatment for gait disturbances. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise can improve daily activity 8 , cardiovascular fitness 8;9 , muscle strength 10 , and fatigue 8;11 in people with MS 12 . Strength training is known to promote neural adaptations that can lead to favorable functional outcomes in MS participants [13][14][15][16] . Since physical rehabilitation is often the only treatment offered to individuals with MS for recovery of function, it is critical to determine what is the most efficient way to improve strength.…”
Section: Introductionmentioning
confidence: 99%